Migrant ethnic identity: concept and policy implications - Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2007)
With globalization, the size of migration and the value of ethnicity is rising. Also Cyprus undergoes a strong process of change while experiencing large inflows of migration. The paper investigates the challenges and the potentials of migration from a European Union perspective. It advocates for a new concept to measure the ethnic identity of migrants, models its determinants and explores its explanatory power for various types of economic performance. The ethnosizer, a measure of ethnic identity, classifies migrants into four states: integration, assimilation, separation and marginalization. Empirical evidence supports its relevance for economic outcomes.
Keywords: 300; Ethnic identity; acculturation; migrant assimilation; migrant integration; cultural economics; Migranten; Ethnische Gruppe; Soziale Integration; Berufliche Integration; Kulturökonomik; Deutschland; EU-Staaten